2016
DOI: 10.1007/s00339-016-9963-4
|View full text |Cite
|
Sign up to set email alerts
|

Growing TiO2 nanowires by solid–liquid–solid mechanism including two factors (Ti and O)

Abstract: Identifying the growth factors of nanowires helps in controlling their structure and morphology and determining their optimal growth conditions. This study investigates the effect of titanium substrate in growing TiO 2 nanowires (NWs) with evaporation method. It reveals that the titanium in substrate is indeed the main source of growth. Using the substrate as the only source of growth with regulated amount of accessible oxygen in the furnace, NWs with lengths ranging from 1 to 70 lm were obtained. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…TiO 2 nanowires (NWs) are another typical onedimensional structure with high sensitivity for detecting certain gaseous species [62,63]. However, wet chemical synthesis methods, such as solid-liquid-vapor (SLV) [64][65][66], thermal oxidation [67,68], hydrothermal [69], sol-gel [70,71], pulsed laser deposition [72,73], electrospinning [74], and anodizing method [75], have a high cost as they require more cleaning processes and the transfer of nanostructures on an appropriate substrate. Moreover, TiO 2 NWs are typically made in the form of a single nanowire.…”
Section: Nanostructured Tiomentioning
confidence: 99%
“…TiO 2 nanowires (NWs) are another typical onedimensional structure with high sensitivity for detecting certain gaseous species [62,63]. However, wet chemical synthesis methods, such as solid-liquid-vapor (SLV) [64][65][66], thermal oxidation [67,68], hydrothermal [69], sol-gel [70,71], pulsed laser deposition [72,73], electrospinning [74], and anodizing method [75], have a high cost as they require more cleaning processes and the transfer of nanostructures on an appropriate substrate. Moreover, TiO 2 NWs are typically made in the form of a single nanowire.…”
Section: Nanostructured Tiomentioning
confidence: 99%
“…Several attempts have been made to synthetize TiO 2 nanowires (NWs) including vapor liquid solid (VLS) [13][14][15][16], thermal oxidation [17][18][19][20], hydrothermal [21], sol gel [12,22], pulsed laser deposition [3,23], electrospinning [24][25][26][27], and anodization method [28]. However, wet chemical methods require further cleaning processes and the nanostructures transfer on an appropriate substrate, which increase the cost of the synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Sani et al [15] demonstrated the VLS growth of TiO 2 NWs on a 50 nm thick Ti buffer layer by using mixed Ti and graphite powder as a source material to reduce the evaporation temperature of Ti. In general, the thermal evaporation processes reported in the literature always require two steps, the sputtering of a Ti buffer layer and the evaporation of Ti at high temperature [16,[29][30][31]. These processes require a high-energy consumption and a complex setup for the nanostructures growth.…”
Section: Introductionmentioning
confidence: 99%